Regeneration of Plantlets Through PLB (Protocorm-Like Body) Formation in Phalaenopsis âJoin Angle X Sogo Musadianâ - Dini Meilasari; Iriawati Iriawati (Institute for Research and Community Services (LPPM) ITB, 2016)
Selection and regeneration of specific hybrids of Phalaenopsis typically takes a long time since this plant usually reproduces through seeds. This study was conducted to examine the best medium and explants for regeneration of Phalaenopsis âJoin Angle X Sogo Musadianâ. In vitro and in vivo roots and leaves were used as explants, which were cultured in half-strength Murashige and Skoog medium supplemented with various combinations of plant growth regulators (TDZ, 2,4-D, NAA, BAP and IAA). The results showed that the in vitro roots produced the highest number of PLBs (49.3 PLBs) when they were cultured in medium containing 0.5 ppm NAA, 5 ppm BAP, and 0.5 ppm IAA. The in vitro leaf explants also regenerated PLBs, however, only two PLBs developed, i.e. when they were cultured in medium containing 1 ppm TDZ and 2 ppm 2,4-D. PLB germination into plantlets was performed by culturing each PLB on MS medium without plant growth regulators. Based on the results of the present study, it can be concluded that in vitro roots and half-strength MS medium supplemented with 0.5 ppm NAA, 5 ppm BAP, and 0.5 ppm IAA are the best explant and best medium respectively for plant regeneration through PLBs.